Pengaruh Return On Equity ( R O E ) , Return On Asset (ROA), Debt To Equity Ratio (DER), dan Earning Per Share (EPS) Terhadap Return Saham 50 Most Active Stocks By Trading Value ( Studi Kasus Di Bursa Efek Indonesia Tahun 2015 - 2018 ) - Eunike Thalia Ariadi Santosa; Bonifatius Junianto Wibowo (Universitas Katolik Soegijapranata, Semarang, 2022)
50 Most Active Stocks by Trading Value were 50 Most Active Stocks traded in Indonesian Stock Exchange according to trading transaction value. The value of those stocks was high and trading volume was so big that it has optimal return for investor. The performance of those firms of 50 Most Active Stocks will determine the fluctuation of stock price that can affect stock return. The purpose of this research was to know the influence of Return on Equity (ROE), Return on Asset (ROA), Debt to Equity Ratio (DER) and Earning per Share (EPS) to Stock Return of the firms of 50 Most active stocks by value trading which listed at Indonesian Stock Exchange from 2015 until 2018. The samples of this research were 16 firms. Those samples were obtained with Purposive Sampling. The data were financial reports and stock price of those 16 firms. The Multiple Regression was used to analyze the data. The result displayed that Return on Equity (ROE) and Earning per Share (EPS) affected positively to Stock Return. Whereas, Return on Asset (ROA) and Debt to Equity Ratio (DER) affected negatively to Stock Return